Effect of Mould and Melt Temperature on the Properties of Styrene Acrylonitrile Moulded Parts - Cahyo Budiantoro; Adi Nugroho (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2018)
The quality of injection moulded parts can be influenced by processing parameters. The effect of mould temperature and melt temperature on the weight and shrinkage of Styrene Acrylonitrile moulded part was observed in this research. It was found that by increasing mold temperatures at constant melt temperature and injection speed, the weight of the part decreased and the shrinkage value slightly decreased. On the other hand, by increasing melt temperature at constant mold temperature and injection speed, the part weight increased. Both mold temperature and melt temperature gave only a small effect because the temperature difference was not too large.